SISTEM INFORMASI PEMANTAUAN PADA PEMELIHARAAN PERANGKAT LAPTOP BERBASIS WEBSITE DI PT KIMIA FARMA TBK - Dani Ali Cahyadi, (2022)
PT. Kimia Farma Tbk which is located on Jl. Veteran No. 9 RT 02 RW 03 which is the place of this research. PT. Kimia Farma is engaged in the pharmaceutical industry which was founded by the Dutch East Indies Government in 1817. Laptop devices that must be maintained in the OPCO IT unit often do not control the amount, because at that time there was no system to record employee laptop devices that would be maintenance at the OPCO IT unit. and still using the manual method, namely attaching a label or sticker to the laptop device that will be repaired, making it easier for the unit to monitor laptop devices based on their repair status. Therefore, there is a need for a website-based monitoring information system for laptop device maintenance. The method used is Agile with Extreme Programming model, and assisted by visual modeling using Unified Modeling Language (UML) to make it easier for users to read a system.